A Material Development of Speech Act as its Contribution For a Vocational High School English Handbook at an Eleven Grade - Algajaladre Nadya Santoso; Laily Nur Affini (Universitas PGRI Semarang, 2019)
Theis research has a prominet goal, idenitfying types of speech acts uttered by an English teacher at a vocational high school. This work uses Searle’s theory to discover the dominant kinds of speech act employed by the teacher. The researchers also investigated the additional utterances in showing learning movement. The research methodology is descriptive-qualitative research, where the researcher found three kinds of speech act uttered by the teacher; directive, representative, and expressive. The researchers calculated the data finding and found 297 utterances which comprised of 246 directives utterances or 82,83% of overall data, 45 representative utterances or represented the 15.15% of data, and 6 expressive utterances which covered 2,02%. The most obtrusive was directive speech acts (82.83%) and the less frequent was expressive speech act (2.02%). The most obtrusive was directive speech acts because the teacher often used directives (questioning) to handle the students in the classroom and made sure that the students understand the aims of the English material.